The snowmelt period in a Mediterranean High Mountain Catchment : runoff and sediment transport - N. Lana-Renault; B. Alvera; J. M. García Ruiz (Cuadernos de Investigación Geográfica, 2013)
Runoff and sediment transport during the snowmelt period (May June, 2004) in the Izas catchment (Central Pyrenees) were studied to obtain a sediment balance and to assess the relative importance of sediment transport during that period. The results demonstrated the importance of the snowmelt period and showed that most sediment was exported in the form of solutes (76% of the total for the May-June time span); 24% was exported as suspended sediment and no bedload was recorded. Suspended sediment mostly occurred during the second phase of the snowmelt period, when an expanding area of the catchment was free of snow. Sediment transport during the snowmelt period represented 43% of the annual sediment yield.